2017
DOI: 10.1016/j.yebeh.2017.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Early-life status epilepticus acutely impacts select quantitative and qualitative features of neonatal vocalization behavior: Spectrographic and temporal characterizations in C57BL/6 mice

Abstract: Early-life seizures are known to cause long-term deficits in social behavior, learning, and memory, however little is known regarding their acute impact. Ultrasonic vocalization (USV) recordings have been developed as a tool for investigating early communicative deficits in mice. Previous investigation from our lab found that postnatal day (PD) 10 seizures cause male-specific suppression of 50-kHz USVs on PD12 in 129 SvEvTac mouse pups. The present study extends these findings by spectrographic characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 31 publications
5
16
1
Order By: Relevance
“…Our results are different from previous studies that described a pattern of decreased call duration in both rat and mouse pups [15,16,18]. In the Lopez-Meraz et al, 2014 study, they found a suppression in the number of USVs in PD14 rats.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our results are different from previous studies that described a pattern of decreased call duration in both rat and mouse pups [15,16,18]. In the Lopez-Meraz et al, 2014 study, they found a suppression in the number of USVs in PD14 rats.…”
Section: Discussioncontrasting
confidence: 99%
“…To assess changes in USV behavior following seizures, we examined USVs on PD12 using the isolation-induced USV paradigm previously described [15,16]. All vocalizations were recorded in the afternoon (between 1 and 5 pm), approximately 24 hours after the last seizure for the HSL paradigm and 48 hours later for the LSL paradigm.…”
Section: Ultrasonic Vocalization Recordingmentioning
confidence: 99%
See 3 more Smart Citations